ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI INDUSTRI KECIL MENENGAH KERAJINAN LOGAM DI KABUPATEN GIANYAR - Indarwasih, Fitri Indarwasih; Marhaeni, A.A. I.N (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.08.TAHUN.2023DO - 10.24843/EEB.2023.v12.i08.p01, 2023)
This study aims to analyze 1) the simultaneous effect of labor, capital and raw materials on the production value of the non-exported and already exported handicraft industry, 2) the partial effect of labor, capital and raw materials on the production of the non-exported and exported handicraft industry, 3) the difference in labor, capital, raw materials and production of industry has not been exported and export. This research was conducted in Gianyar Regency. The samples is 262 units of the company, with purposive sampling method with descriptive analysis techniques, multiple linear regression and paired t-test sample difference test. Results shows that labor, capital and raw materials simultaneously affect the production of export and non-export metal handicraft industry. Labor and raw materials partially have a positive and significant effect on the production value of the export metal craft industry, while capital has no and significant effect on the production value of the export metal craft industry. Labor and capital partially have a positive effect on the production value of the non-exported metal craft industry, while raw materials have no positive effect on the production value of the non-exported metal craft industry. There are significant differences in the use of labor, capital, raw materials and production values ??used that export and those that have not been exported.